Plasmablastic Lymphoma or Plasmablastic Myeloma: A Case of Post-Transplant Lymphoproliferative Disorder - Ramadas, Poornima; Williams, Michael; Duggan, David B. (Case Reports in Hematology, 2021)
Plasmablastic lymphomas and plasmablastic myelomas are malignancies with overlapping clinical and pathological features which pose a diagnostic dilemma and are known to be aggressive with a poor outcome. CD38 is a common immunophenotypic maker for both these malignancies and provides a rationale for using daratumumab-based regimes. We describe a 57-year-old male with a history of end-stage renal disease who underwent a deceased-donor renal transplant maintained on chronic immunosuppression who presented with ascites and was found to have abdominal adenopathy and a lytic lesion in the humerus and diagnosed with a post-transplant lymphoproliferative disorder with features intermediate between plasmablastic lymphoma and plasmablastic myeloma. The patient was subsequently treated with a daratumumab-based regime with an excellent response. This case highlights a rare scenario that poses a diagnostic and therapeutic challenge. As there is no standard of care for the treatment of both these malignancies, this case report also describes the use of daratumumab with a good long-term outcome, especially when the pathological distinction between the two entities is difficult.